Упростите выражение (6 5/12-2/3+1/12)*3/4​

zimina31 zimina31    3   19.06.2020 17:59    3

Ответы
nastyyanokogloStasya nastyyanokogloStasya  15.10.2020 14:29

Пошаговое объяснение:

(6 5/12-2/3+1/12)*3/4

1) 6\frac{5}{12} -\frac{2}{3} ==\frac{77}{12} -\frac{2}{3} =\frac{77-8}{12} =\frac{69}{12}=\frac{23}{4}

2)\frac{23}{4} +\frac{1}{12} =\frac{69+1}{12} =\frac{70}{12} =\frac{35}{6}

3) \frac{35}{6} *\frac{3}{4} =\frac{35}{8} =4 \frac{3}{8} =4,375

ответ: 4,375.

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика